Effect of argon-ion irradiation on cavity formation in 18Cr10NiTi austenitic steel and its strengthened version - Kolodiy, I.V.; Karpov, S.A.; Kalchenko, A.S.; Kopanets, I.E.; Tikhonovsky, M.A.; Tolstolutskaya, G.D.; Velikodnyi, A.N.; Voyevodin, V.N. (Вопросы атомной науки и техники, 2020)
The swelling behavior of 18Cr10NiTi austenitic stainless steel and its strengthened by Y₂O₃-ZrO₂ nanooxides version irradiated with 1.4 MeV Ar-ions up to dose 30 displacements per atom (dpa) with simultaneously implanted argon to the levels 200 appm at temperatures of 550...650 ºC was investigated. Transmission electron microscopy (TEM) has been used to study the resulting microstructure evolution. Cavities were observed in both materials. The overall swelling of ODS 18Cr10NiTi steel reaches 0.1% which is about half as much as conventional 18Cr10NiTi steel. Досліджено розпухання аустенітної нержавіючої сталі Х18Н10Т і її дисперсно-зміцненої нанооксидами системи Y₂O₃-ZrO₂-версії, опромінених енергетичними іонами Ar з енергією 1,4 МеВ до дози 30 зміщінь на атом (зна) з одночасно імплантованими атомами аргону до 200 appm у діапазоні температур 550…650 ºC. Для вивчення еволюції мікроструктури була використана просвічуюча електронна мікроскопія (ПЕМ). Порожнини спостерігалися в обох матеріалах. Загальне розпухання ДЗО Х18Н10Т сталі досягає 0,1%, що приблизно вдвічі менше, ніж для звичайної стали Х18Н10Т. Исследовано распухание аустенитной нержавеющей стали Х18Н10Т и ее дисперсно-упрочненной нанооксидами системы Y₂O₃-ZrO₂-версии, облученных энергетичными ионами Ar с энергией 1,4 МэВ до дозы 30 смещений на атом (сна) с одновременно имплантированными атомами аргона до 200 appm в диапазоне температур 550…650 ºC. Для изучения эволюции микроструктуры была использована просвечивающая электронная микроскопия (ПЭМ). Полости наблюдались в обоих материалах. Общее распухание ДУО Х18Н10Т стали достигает 0,1%, что примерно вдвое меньше, чем в обычной стали Х18Н10Т.